Prison prescribing practice: practitioners' perspectives on why prison is different. Issue 4 (April 2014) - Bartlett, A.; Dholakia, N.; England, R.; Hales, H.; van, E.; McGeorge, T.; Moss, B.; Ovaisi, S.; Tukmachi, E.; Patel, S.
<x xml:space="preserve">Abstract</x> The current prison population in England and Wales has multiple, complex healthcare needs, presenting unique challenges to those caring for prisoners. Prison numbers have increased dramatically in the last 10 years. There are now approximately 84, 000 prisoners in England and Wales 1 and 120, 000 new episodes of imprisonment each year 2. The authors all contribute to prison healthcare. Below, we discuss a key issue arising from first‐hand experience of prisoners' health and social care needs, the prescription of psycho‐active drugs by primary and secondary care practitioners. This is a core medical task, but beset with difficulties. These difficulties are not necessarily encountered in other areas of prison healthcare. However, they do illustrate how providing healthcare to prisoners is complex, often lacking a research base and can have pitfalls that are not obvious to the outsider.